Tuberculosis-induced acute respiratory distress syndrome treated with veno-venous extracorporeal membrane oxygenation. (2019) - Binh, Nguyen Gia; Manabe, Toshie; Co, Dao Xuan; Thach, Pham The; Tuan, Dang Quoc; Cuong, Bui Van; Tuyet, Le Thi Diem; Kudo, Koichiro; Anh, Nguyen Quoc
Abstract: Tuberculosis (TB) is a rare but known cause of acute respiratory distress syndrome (ARDS) with a high mortality. Veno-venous extracorporeal membrane oxygenation (VV-ECMO) may be an alternative option for treating TB-induced ARDS. However, the literature on TB-induced ARDS treated with VV-ECMO is limited and the most of them were prolonged therapy. We report on a-48-year-old man with TB-induced ARDS who was successfully treated by short-term use of VV-ECMO (5 days). He was developed symptoms and hospitalized with severe dyspnea in a local hospital for 3 days before admission to our hospital. At the time when he was transferred to our hospital, his chest computed tomography showed bilateral, diffuse and consolidative shadows all over the lungs, the ratio of partial pressure of arterial oxygen to the fraction of inspired oxygen (PaO2 /FiO2 ) was 50 mmHg, and respiratory system compliance was 12.5 mL/cmH2 O. Two days after admission, Mycobacterium tuberculosis was detected by a sputum smear examination and he was diagnosed with TB-induced ARDS. VV-ECMO support was then initiated with administration of anti-TB drugs and systemic corticosteroid treatment. On the 4 th day of ECMO support, his PaO2 /FiO2 increased to 400 mmHg and lung compliance increased to 45 mL/cmH2 O. He was weaned from ECMO on the 5th day of ECMO support and was extubated at the 8th day. He was discharged from hospital on the 47th hospitalized day and continued anti-TB medication at home. VV-ECMO is effective for TB-induced ARDS even in short-term administration if progression of ARDS is rapid.